ANALISIS STRATEGI PEMASARAN PADA WARUNG MAKAN TAKODO DALAM MENGHADAPI PERSAINGAN BERBASIS SWOT - Andi; Isak Pasulu; Grace Sriati Mengga (JURNAL ILMIAH EDUNOMIKA, 2025)
ABSTRACT This study aims to analyze the marketing strategies implemented by Warung Makan Takodo in facing competition within the rapidly growing local culinary industry. The research employed a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews with the owner, employees, and customers, as well as observation and documentation, and analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework. The strengths identified include its strategic location in front of Pasar Baru Makale, authentic local menu such as kapurung and green bean porridge, cleanliness, comfortable atmosphere, friendly service, and high customer loyalty. Weaknesses comprise suboptimal operational management, limited staff during peak hours, lack of digital promotion, delays in raw material supply, and minimal innovation in modern menu items. Opportunities arise from the popularity of local and spicy food among young people, increasing economic activity around the market, positive impacts from Toraja cultural events and tourism, and the growth of social media and pre-order services. Threats include price competition, changing consumer preferences, rising raw material prices, dependency on market supplies, and the demand for digital services. The recommended strategies focus on optimizing strengths to seize opportunities, addressing weaknesses through opportunity utilization, using strengths to counter threats, and minimizing weaknesses while anticipating threats. Keywords: marketing strategy, SWOT analysis, food stall, competition, local culinary